Modern drying technology. - Tsotsas, Evangelos, ....-; Mujumdar, Arun S., ....- (Weinheim : Wiley, 2007)
This five-volume handbook provides a comprehensive overview of all important aspects of modern drying technology, including only advanced results. Volume 1 deals with computational tools at different scales, including homogenized, pore network and continuous thermo-mechanical models, computational fluid dynamics and population balances, as well as process systems simulation tools. High-level, cutting-edge results on a mandatory industrial process.Volume 2 brings together the key methods used for drying by a variety of industries. Key topics include the measurement of average moisture content, which covers acoustic levitation, dew point mirror and coulometry, near-infrared spectral imaging, magnetic resonance imaging and X-ray tomography. Characterisation of particles using positron emission particle tracking and submicron scale methodology are also discussed. Both single particle and particle systems are explained and clarified with real examples.Volume 4: This multivolume work covers drying, a key industrial processes that accounts for about 10-percent of total energy consumption in industry. It guides engineers towards achieving energy savings through such approaches as improved apparatus design, optimization, and heat recovery. In so doing, it points the way to success for both researchers and practitioners in mastering this multiphase and multiscale process.
Vol.1: Computational tools at different scales - Vol.2: Experimental techniques -Vol.3: Product quality and formulation - Vol.4: Energy savings